Development and Validation of Canva-Based Learning Media for Improving Early Reading Skills in Children Aged 5–6 - Rahma Rahma; Salpina Salpina; Darmiati Darmiati; Anisaturrahmi Anisaturrahmi (Journal of General Education and Humanities, 2026)
Early reading skills are a fundamental aspect of emergent literacy and play an important role in children's future academic success. However, observations at Harapan Bunda Preschool revealed that literacy learning activities still relied primarily on printed books and student worksheets, while the use of digital learning media remained limited. This study aimed to develop and validate Canva-based learning media to support early reading activities among children aged 5–6 years. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 10 children aged 5–6 years enrolled in Harapan Bunda Preschool. Data were collected using media validation sheets, material validation sheets, teacher response questionnaires, and observation sheets to assess children's early reading skills. The validation results showed that the Canva-based learning media received feasibility scores of 91% from media experts and 93% from material experts, both categorized as very feasible according to the established validation criteria. During implementation, the same group of children participated in both the small-group and large-group trial stages. Observation scores increased from 48.75% in the initial trial stage to 90% in the subsequent implementation stage. These findings indicate that the developed Canva-based learning media is feasible and appropriate for supporting early reading activities in preschool settings. Further studies using experimental designs are recommended to examine its effectiveness in improving children's reading outcomes.